Perlindungan Hukum Terkait Upah Pekerja Rumah Tangga (Prt) Berdasarkan Undang-Undang Nomor 13 Tahun 2003 Tentang Ketenagakerjaan - Ramadani, Atifa Awdia (Jurnal Khazanah Intelektual, 2024)
The purpose of this study is to analyze legal protection related to wages for domestic workers in Law Number 13 of 2003 concerning Manpower. This research uses an analytical descriptive method with a normative juridical approach, then the data obtained is analyzed qualitatively. The results obtained are that the wages of workers regulated in Law Number 13 of 2003 concerning Manpower are only intended for formal sector workers and have excluded domestic workers from the regulation. Regulation of the Minister of Manpower No. 2/2015 on the Protection of Domestic Workers (Permenaker PPRT) as one of the regulations protecting domestic workers has not provided optimal protection for domestic workers due to the option to make verbal agreements. Work agreements that are only made verbally with a basic understanding of each other's roles cause clarity regarding domestic workers' rights, such as the wages they receive, to be unclear. A step that can be taken considering the peculiarities of the domestic work sector is the formalization of the employment relationship, by requiring the requirement of a written employment contract or written statement of information, including normal working hours, overtime requirements, wages, including payment in kind if any, agreed deductions, and wage periods and payment methods. Keywords: Legal Protection; Wages; Domestic Workers.